2000
DOI: 10.1046/j.1432-1327.2000.01462.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, cloning, and characterization of porcine nucleoside triphosphate diphosphohydrolase‐1

Abstract: In this study, we have investigated the distribution of the enzyme nucleoside triphosphate diphosphohydrolase-1 (NTPDase1; EC 3.6.1.5) in a subset of pig tissues by biochemical activity and Western blotting with antibodies against porcine NTPDase1. The highest expression of this enzyme was found in vascular endothelium, smooth muscle, spleen and lung.The complete cDNA of NTPDase1 from aorta endothelial cells was sequenced using primer walking. The protein consists of 510 amino acids, with a calculated molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Furthermore, nothing is known about the functional integration of either NTPDase1 or NTPDase2 with each other or other ectonucleotidases/NTPDases. Biochemical analyses of murine and porcine cardiac tissues have demonstrated ATPase/ ADPase ratios of 10, suggesting expression of enzymes with preferential ATPase activity (this paper and Lemmens et al 29 ). Given the levels of NTPDase2 messenger RNA (mRNA) expression in murine and human hearts, this enzyme would be a likely candidate responsible for such an activity.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, nothing is known about the functional integration of either NTPDase1 or NTPDase2 with each other or other ectonucleotidases/NTPDases. Biochemical analyses of murine and porcine cardiac tissues have demonstrated ATPase/ ADPase ratios of 10, suggesting expression of enzymes with preferential ATPase activity (this paper and Lemmens et al 29 ). Given the levels of NTPDase2 messenger RNA (mRNA) expression in murine and human hearts, this enzyme would be a likely candidate responsible for such an activity.…”
Section: Introductionmentioning
confidence: 68%
“…These data are comparable to prior observations in pig tissues. 29 To identify the relative contribution of NTPDase1 to the total NTPDase activities in heart tissues, we then contrasted the activity of homogenates derived from cd39 ϩ/ϩ and cd39 Ϫ/Ϫ tissues. Both ATPase and ADPase activities in cardiac tissue preparations from NTPDase1-null mice were not significantly different in wild-type tissues.…”
Section: Ntpdase Activity In Mouse Hearts and Transfected Cellsmentioning
confidence: 99%
“…No staining was seen in the hepatic parenchyma. Thus, similar to its vascular distribution in other systems, 8,9 NTPDase1 is restricted to vascular endothelia within the liver. Fig.…”
mentioning
confidence: 69%
“…[5][6][7] Several of these enzymes have been cloned and characterized at the molecular level. NTPDase1 has been identified as a vascular NTPDase expressed at endothelial and leiomyocyte plasma membranes 8,9 and is a critical regulator of platelet aggregation. 10 NTPDase2 is an NTPDase that is expressed by epithelial organs and cell lines, 11,12 but its specific physiologic function is unknown.…”
mentioning
confidence: 99%
“…The majority of the ecto-ATPDases that have been cloned are closely related to CD39, a cell surface antigen that is expressed on activated lymphocytes [11,12]. CD39s from several species have 60-90% identity in their primary sequences [12][13][14][15]. Biochemical and immunolocalization studies indicated that CD39s are vascular ecto-ATPDases [16][17][18][19][20].…”
mentioning
confidence: 99%